2020
DOI: 10.1186/s12896-020-00615-0
|View full text |Cite
|
Sign up to set email alerts
|

Translational regulation of periplasmic folding assistants and proteases as a valuable strategy to improve production of translocated recombinant proteins in Escherichia coli

Abstract: Background Advantages of translocation of recombinant proteins to the periplasm in Escherichia coli include simplified downstream processing, and improved folding and in vivo activity of the target protein. There are, however, problems encountered in the periplasmic production that can be associated with the incorrect formation of disulfide bonds, incomplete cleavage of the signal peptide, and proteolytic degradation. A common strategy used to overcome these difficulties involves manipulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Co-producing LepB, which cleaves off signal peptides upon protein translocation, can also increase periplasmic protein production yields ( van Dijl et al, 1991 ). It has been shown that increasing the synthesis of protease IV (SppA) by modifying its TIR also results in enhanced periplasmic protein production ( Gawin et al, 2020 ). SppA is a membrane-bound signal peptide peptidase that is required for maintaining proper protein secretion ( Novak and Dev, 1988 ; Dalbey et al, 2012 ).…”
Section: Strategies To Enhance Periplasmic Protein Production Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-producing LepB, which cleaves off signal peptides upon protein translocation, can also increase periplasmic protein production yields ( van Dijl et al, 1991 ). It has been shown that increasing the synthesis of protease IV (SppA) by modifying its TIR also results in enhanced periplasmic protein production ( Gawin et al, 2020 ). SppA is a membrane-bound signal peptide peptidase that is required for maintaining proper protein secretion ( Novak and Dev, 1988 ; Dalbey et al, 2012 ).…”
Section: Strategies To Enhance Periplasmic Protein Production Yieldsmentioning
confidence: 99%
“…Rather than deleting the gene encoding DegP or inactivating its protease function, periplasmic protein production yields have also been improved by lowering DegP levels. This was done by replacing the ribosome binding site in the TIR controlling degP expression with a weaker one ( Gawin et al, 2020 ).…”
Section: Strategies To Enhance Periplasmic Protein Production Yieldsmentioning
confidence: 99%
“…Among them, SecB-dependent and SRP-mediated pathways both complete the translocation process by binding to SecA, and genetic fusion of signal peptides to RPs can enable them to utilize these pathways to translocate. Commonly used signal peptides include pelB, OmpA and DsbA [89,90], but each signal peptide triggers a different mechanism that greatly affects the effectiveness of RP transport. In contrast to SRP-mediated DsbA, SecB-dependent OmpA drives the synthesis of endogenous secreted and membrane proteins, preventing Sec translocator saturation [89].…”
Section: Enhancement Of Post-translational Modificationsmentioning
confidence: 99%
“…For proteins that require expression in defined genetic backgrounds, or when periplasmic expression is preferred, cell envelope folding catalysts can be overexpressed by means of modifying their native RBS strength (Gawin et al, 2020), or by introducing an exogenous gene copy on a plasmid. pTUM4 is such as plasmid;…”
Section: Aid Ing Protein Fold Ing By Us Ing the Ds B Protein S E Xog Enous Lymentioning
confidence: 99%
“…For proteins that require expression in defined genetic backgrounds, or when periplasmic expression is preferred, cell envelope folding catalysts can be overexpressed by means of modifying their native RBS strength (Gawin et al., 2020), or by introducing an exogenous gene copy on a plasmid. pTUM4 is such as plasmid; it constitutively overexpresses both DsbA and DsbC, as well as the folding chaperones SurA and FkpA, to aid expression of difficult proteins (Schlapschy et al., 2006; Shriver‐Lake et al., 2017).…”
Section: Aiding Protein Folding By Using the Dsb Proteins Exogenouslymentioning
confidence: 99%